The Effect of Mediterranean Diet on Body Composition, Inflammatory Factors, and Nutritional Status in Patients with Cachexia Induced by Colorectal Cancer: A Randomized Clinical Trial - Amir Bagheri PhD; Farzaneh Asoudeh MSc; Saied Rezaei MD; Mohammad Babaei MD; Ahmad Esmaillzadeh PhD (Integrative Cancer Therapies, 2023)
Background: Along with high calorie and high protein diet, a new comprehensive dietary approach is needed to control cachexia caused by cancer and its related outcomes. This study was done to evaluate the effect of a Mediterranean diet on body composition, nutritional status, and inflammatory markers among cancer cachexia patients. Methods: In this randomized clinical trial, 46 patients with colorectal cancer-induced cachexia were included. After randomization, 23 patients were allocated to the intervention group (Mediterranean diet) and 23 to the control group (nutritional counseling for weight gain and prevention of weight loss in cancer patients). The primary outcome including muscle health, nutritional status, and inflammatory markers along with secondary outcomes such as quality of life, and serum proteins were evaluated at the start and the eighth week of the study. Statistical analysis was performed according to the intention-to-treat concept. To compare changes in dependent variables between the 2 groups, analysis of covariance (ANCOVA) was performed. Results: After adjustment for the baseline values, age, sex, and supplements use, in the Mediterranean diet group mean of weight ( P  < .001), lean body mass ( P  = .001), fat mass ( P  = .002), and muscle strength ( P  < .001) were significantly increased compared to the control group. Regarding inflammatory markers, the mean serum level of tumor necrosis factor-alpha (TNF-α) ( P  < .001), high sensitive-C-reactive protein (hs-CRP) ( P  = .01) and Interleukin 6 (IL-6) ( P  < .001) were significantly improved in the Mediterranean diet group. Moreover, in the Mediterranean diet group, the score for global health status ( P  = .02) and physical performance score ( P  < .001) were significantly increased. Conclusion: It appears that the implementation of the Mediterranean diet might be a strategy to improve nutritional status, quality of life, inflammatory markers, and body composition in patients with colorectal cancer cachexia. Trial registration: Iranian Registry of Clinical Trials ( www.irct.ir ); ID: IRCT20211027052884N1